The Study of Relationship between Social Capital and Political Tolerance (Case Study: Shiraz University) - jahangir jahangiri; khalilallah sardarnia; ghasem alizadeh (توسعه اجتماعی, 2016)
Social capital with emphasis on trust and social networks is one of the important prerequisites for social integration and democracy. The purpose of this study is investigating the relationship between social capital and political tolerance. In this study, theory of social capital from Putnam was used for variable of social capital and King’s theory for political tolerance as a theoretical framework. In this research, survey method was used. This study has been done upon 390 of college students. The results show 19.2 percent of students with low level of political tolerance, 61.3 percent with average political tolerance and 19.5 percent with high level of political tolerance. Variables such as social participation, social interaction, social commitment, social awareness, social trust, media consumption, religious practice, age and level of education had significant relationship with political tolerance. However, marital status, educating university, ethnicity, residence, place of birth, parents' education, gender and employment status had no significant relationship with political tolerance. The results of stepwise regression in the multivariate regression showed the variables such as community involvement, social awareness, social interaction, place of birth, social trust, place of residence, gender and media consumption explained 24 percent of the variance in the dependent variable.